2019
DOI: 10.2136/vzj2019.06.0063
|View full text |Cite
|
Sign up to set email alerts
|

Development and Uncertainty Assessment of Pedotransfer Functions for Predicting Water Contents at Specific Pressure Heads

Abstract: PTFs for water contents at specific pressure heads were developed. Covariate shift increased uncertainty in PTF predictions. Relative importance of predictors in machine learning PTFs was determined. There has been much effort to improve the performance of pedotransfer functions (PTFs) using intelligent algorithms, but the issue of covariate shift, i.e., different probability distributions in training and testing datasets, and its impact on prediction uncertainty of PTFs has been rarely addressed. The common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
0
5
0
1
Order By: Relevance
“…It was observed a great symmetry exists in T soil , WC soil, , and air temperatures as their skewness values were close to zero; however, significant positive skewness for CO 2 and N 2 O fluxes indicated that mean values were greater than the median of data. The distributions of RH max and N 2 O with high values of kurtosis (>2) demonstrated the existence of high peaks around the mean and minor peaks in their long tails (Kotlar, de Jong van Lier, et al., 2019). Kurtosis and standard deviation of N 2 O for NCC scenario were slightly less than CC, showing suppressed peak and heavier shoulder of distribution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed a great symmetry exists in T soil , WC soil, , and air temperatures as their skewness values were close to zero; however, significant positive skewness for CO 2 and N 2 O fluxes indicated that mean values were greater than the median of data. The distributions of RH max and N 2 O with high values of kurtosis (>2) demonstrated the existence of high peaks around the mean and minor peaks in their long tails (Kotlar, de Jong van Lier, et al., 2019). Kurtosis and standard deviation of N 2 O for NCC scenario were slightly less than CC, showing suppressed peak and heavier shoulder of distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Here, input attributes were initially mapped into a higher‐dimensional feature space using a mapping or so‐called kernel function. Then SVM found an optimal hyperplane in this multi‐dimensional space separating the mapped data with the largest margin (Kotlar, de Jong van Lier, et al., 2019). This study considered linear, polynomial, and radial basis kernel functions, respectively, called SVML, SVMP, and SVMR.…”
Section: Methodsmentioning
confidence: 99%
“…The 102 soil samples were shuffled (Kotlar et al, 2019b) using the MATLAB software package (MathWorks, Makers of MATLAB and Simulink, 2021). Before developing the models, the shuffled data were imported to the Unscrambler X v. 9.7 software package (CAMO, Technologies Inc., 2013) and randomly divided into the calibration and validation datasets, containing nearly 75 % (76 samples) and 25 % (26 samples), respectively.…”
Section: Models Developmentmentioning
confidence: 99%
“…Parameter tuning of the ranger was performed with the "caret" R package (Kuhn et al, 2017(Kuhn et al, , 2018. With the im-plemented train function, a fivefold cross-validation was repeated 10 times to tune the number of randomly selected predictor variables at each split (mtry) and find the best performing splitting rule (splitrule) during training.…”
Section: The Random Forest Algorithm To Derive Ptfsmentioning
confidence: 99%